(3HQfGeL EQTGOi dJfejI GdOGaYjI ddEfLGR dOi CWaGd GdQhVI Phi UYhHGJ GdJYde HGdLeGgQjI GddjHjI (B= s A counseling program for enhancing achievement motivation among kindergarten with learning disabilities in Libya - (3YeQh Ydi YeQ NdjaI s; (3HWQS MGaX HWQS (B: s; (3SgjQ cGed GMeO (B: s ((3GdbGgQI (B: s (3YeQh Ydi YeQ NdjaI (B: s, 2012)
(3gOaJ GdOQGSI Gdi GYOGO HQfGeL dJfejI GdOGaYjI ddEfLGR dOi CWaGd GdQhVI Phi UYhHGJ GdJYdje HGdLeGgjQjI GddjHjI hGdJYQa Ydi eOi aGYdjI GdHQfGeL GdeSJNOe ai GdOQGSI GdMGdjI hJchfJ YjfI GdOQGSI ef (B13 (3Wad ef Phi UYhHGJ GdJYdje hjJQGhM YeQge GdRef ef (B5-6 (3SfhGJ hGSJNOeJ GdOQGSI GNJHGQ QBaf ddPcGA hHWGQjI UYhHGJ GdJYde GdfeGFjI dGWaGd GdQhVI hGNJHGQ GdOGaYjI ddGfLGR dOi Wad GdQhVI hHQfGeL JfejI GdOGaYjI GdGfLGR dOi GdGWaGd Phi UYhHGJ GdJYde hbO GhVMJ GdfJGFL Gf GSJNOGe GdHQfGeL GdebJQM cGf dg GKQ GjLGHi ai JfejI GdOGaYjI ddGfLGR dOi CWaGd GdQhVI Phi UYhHGJ GdJYdes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI QjGV GdCWaGd (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CWaGd GdQhVI s; (3GdOGaYjI ddEfLGR s; (3UYhHGJ GdJYde s